Impact of Big 5 Personality & Intelligence on Transformational Leadership Process and Managerial Performance: A Case of the Middle East Gulf Region - Sumadi, Mohammad Ahmad (2024)
The objective of this study was to investigate the impact of emotional intelligence (EI) and the Big Five personality traits on the attainment of success in leadership positions within hospital administration. The researchers predicted the association between emotional intelligence (EI) and neuroticism, anticipating a negative link. Additionally, they projected a positive relationship between EI and the Big Five personality traits, specifically openness to experience, agreeableness, openness to new ideas, and extraversion. The primary objective of this study is to fill a void in the existing body of research by examining the relationship between personality, emotional intelligence (EI), and leadership effectiveness and performance. Our results indicate that the association between individual differences, leadership, and performance exist. This study did not examine the firm’s performance metrics, but the disturbances’ absorption of measurement errors in the endogenous regressors, which are independent of the exogenous, and minimize coefficient estimate biasesas as held by (Antonakakis et al., 2020). Individual predictors had a low to moderate effect on variation, but their aggregate influence accounted for 56% of transformational leadership variance and 26% of management leadership effectiveness variance. Our study supported merits consideration due to the implementation of controls such as age and managerial experience, the utilization of a longitudinal measure of effectiveness, and the mitigation of common method variance through the use of measures from different sources for predictors and criteria.